SPECIAL FEATURES OF THE SPACE PLANNING SOLUTION OF A MOBILE DOME HOUSE MADE OF WOOD (Collection of scientific works «Modern structures of metal and wood», 2024)
We propose a variant of the space-planning solution of a two-story dome house, which  is  related  to  the  structural  one,  based  on  a  certain  number  of  typical  building  structures: columns, floor panels and, of course, the bearing elements of the dome, which allows assembling the “key ready” building in a few weeks, without the use of heavy construction equipment. A geodesic grid with a hexagonal cell distributes the stresses evenly over the entire surface of the dome, the sphere of which has the smallest ratio of the area of the external walls to the internal volume among all the figures of the same capacity. Thus, with the minimum total area of walls and roof, there is a minimum of the energy consumption for temperature and humidity control in the room. The house, with a foundation diameter of 12 m, is designed for a family of 4–5 people. The structural scheme of the house is mixed and consists of a self-supporting wooden dome frame and interior columns, on which a flat-slab floor of cross-beam panels supported at the corners rests. The dome framework is made of standard rectilinear glued wood parts, which are connected by the steel connectors to form hexagonal cells that allow for window openings anywhere on the surface. The distribution of the internal hemisphere space provides the opportunities that you do not have in classical design. The features of the curved wall surface are considered in the design of the designer furniture, which can emphasize your individuality.